Effect of nitrogen on tensile flow behaviour of type 316 LN austenitic stainless steel. (July 2015) - Ganesan, V.; Laha, K.; Parameswaran, P.; Nandagopal, M.; Mathew, M. D.
Abstract : The influence of nitrogen content on the tensile flow behaviour of type 316 LN austenitic stainless steel has been studied. Nitrogen content in the steel has been varied in the range 0·07 to 0·22 wt-%. Tensile tests were carried out over the temperature range of 300–1123 K at a nominal strain rate of 3×10 −3 s −1 . The tensile flow behaviour of the steels has been analysed based on the constitutive equation proposed by Voce. The Voce's parameters of initial stress (σi ) and saturation stress (σs ) were found to increase linearly with increase in nitrogen content at all the test temperatures. Tensile properties of the steels were predicted from Voce constitutive equation parameters.